Available evidence on risk factors associated with COVID-19's poorer outcomes, worldwide and in Brazil - Bruna Rinaldi; João Pedro S. N. Rinaldi (Hospital de Clínicas de Itajubá, 2020)
Objectives: Analyse availability and quality of existing evidence on COVID-19's risk factors and underlying health conditions that are associated with poorer outcomes, worldwide and in Brazil. Methods: EBMR (Ovid), Google Scholar, MEDLINE (OvidSP), PubMed, CINAHL (EBSCO) and Cochrane Library databases were screened, plus Brazilian government epidemiological reports. A body of 25 articles plus 1 report met the inclusion criteria. Results: Available data are still disconnected and several biases exist throughout literature, mainly due to COVID-19 novelty aspect. Hypertension was the most analysed risk factor, followed by diabetes and chronic obstructive pulmonary disease. Availability of Brazilian data is significantly scarce and only governmental reports are readily available. Conclusion: Further studies, with good methodological designs, are needed to provide good levels of evidence in order to provide solid background to help the pandemic's mitigation strategies.